A Case of Idiopathic Orbital Inflammation And Third Nerve Palsy: Interesting Case - Rajeev Tuli; Indu Dhiman (Delhi Journal of Ophthalmology)
Purpose: This case is a unique presentation of idiopathic orbital inflammation and 3rd nerve palsy (superior division involvement). Case report: A 30 years female patient presented with chief complaints of diplopia for two days and drooping of right upper eyelid for one day. Patient also complained of ocular pain and headache for preceeding ten days. Considering the clinical presentation, a differential diagnosis of thyroid orbitopathy, ocular myasthenia, orbital neoplasm and idiopathic orbital inflammatory syndrome (IOIS) was considered. Laboratory investigations revealed nothing significant. MRI orbit was suggestive of IOIS. The patient was started on oral steroids and had a favorable outcome. Conclusion: Understanding of the clinical features of patients with IOIS, differentiating it from other clinical conditions and timely implementation of available treatment may help to prevent visual loss and other associated morbidity from this condition.